Meridiorhantus Balke, Hájek & Hendrich, 2017, n. gen. - Balke, Michael; Hájek, Jiří; Hendrich, Lars (Zenodo, 2017)
Meridiorhantus n. gen. Type species: Dytiscus calidus Fabricius, 1792 by present designation. Diagnosis . Medium sized to large (12–17 mm) species. Medial labral emargination deep. Sides of pronotum with border thin, often indistinct or partly lacking; posterior pronotal angles weakly obtuse elytral reticulation simple, consisting of fine isodiametric cells and without larger polygonal meshes. Setae on parameres apically acute, not modified to trumpet-shaped “suction” setae (Balke 1990). Position. Sister group of Carabdytes Balke, Hendrich & Wewalka, 1992 (Morinière et al. 2016) (Fig. 1). Etymology. Composed from prefix Meridio -, derived from Latin meridiem (= southern) and stem Rhantus , genus of Colymbetinae; gender masculine. Species composition. Five species distributed in the southern Neotropical region, one of whĺch has two subspecĺes; the only exception is M. calidus (Fabricius, 1792) n. comb. which is widely distributed in the Neotropical Region and reaching also Nearctic regions in Mexico, the southern USA and the E coast of the USA as far north as New York City. Meridiorhantus antarcticus (Germain, 1854) n. comb. M. antarcticus antarcticus (Germain, 1854), Chile (Fig. 3 B). M. antarcticus nahueli Trémouilles, 1984, Argentina. Meridiorhantus calidus (Fabricius, 1792) n. comb. , South and Central America, West Indies, southern USA (Fig. 3 C). Meridiorhantus limbatus (Aubé, 1838) n. comb. , Brazil Notes: This species was not included in Morinière et al. (2016). It is morphologically however very similar to M . antarcticus and M. orbignyi (Balke 1993a) which leads us to conclude that it belongs to this clade as well. Meridiorhantus orbignyi (Balke, 1992) n. comb. , Argentina, Brazil, Uruguay. Meridiorhantus validus (Sharp, 1882) n. comb. (Fig. 3 D), Argentina, Chile. Published as part of Balke, Michael, Hájek, Jiří & Hendrich, Lars, 2017, Generic reclassification of species formerly included in Rhantus Dejean (Coleoptera, Dytiscidae, Colymbetinae), pp. 91-100 in Zootaxa 4258 (1) on page 97, ...